1998
DOI: 10.1002/(sici)1521-396x(199806)167:2<419::aid-pssa419>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation of UHP-Based Fe20Cr5Al Alloys

Abstract: UHP-base alloys have been used to study the effects of sulfur and yttrium on the oxidation resistance of ferritic Fe20Cr5Al alloys. Doping with sulfur and/or yttrium gave a series of alloys with sulfur contents between 0.2 to 50 ppm sulfur, with or without yttrium (0.1 wt% maximum). The a-alumina scale and the metal±oxide interface structures were investigated after oxidation between 1060 and 1350 C (1 to 100 h), using several techniques: SEM, TEM, STEM and Scanning AES. It was found that sulfur contents lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The effect of Pt on S segregation in b-NiAl has also been investigated, and Pt was found to reduce S segregation to the free surface [18][19][20] and even eliminate S at the interface [18]. Hf, a reactive element, is expected to reduce, if not eliminate, S segregation to the interface, as has been found for Zr in Fe 3 Al [21] and Y in FeCrAl [22][23][24]. Hf has been shown to segregate to the Al 2 O 3 /NiAl interface (K. L. More, private communication, unpublished results), but whether it stops S segregation has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of Pt on S segregation in b-NiAl has also been investigated, and Pt was found to reduce S segregation to the free surface [18][19][20] and even eliminate S at the interface [18]. Hf, a reactive element, is expected to reduce, if not eliminate, S segregation to the interface, as has been found for Zr in Fe 3 Al [21] and Y in FeCrAl [22][23][24]. Hf has been shown to segregate to the Al 2 O 3 /NiAl interface (K. L. More, private communication, unpublished results), but whether it stops S segregation has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier work 5) it has been found that carbon together with sulphur tend to segregate to the scale/metal interface, hence deteriorating the scale adhesion. In the present work the impurities of C and N were found to form carbonitride precipitates by reaction with the minor additions of Ti and Zr, or, in the absence of the latter, with the alloy Cr.…”
Section: Discussionmentioning
confidence: 98%
“…The second important RE-effect is attributed to prevention of the deleterious sulphur segregation to the scale/metal interface. 5) Although plenty of scientific literature exists on the REeffect, some of the data extremely important for industrial manufacturing of the FeCrAl alloys are still not available. In particular, little is known about the interaction of the RE with common alloy impurities other than sulphur.…”
Section: Introductionmentioning
confidence: 99%
“…It was evident a priori that the conventional procedure established for the formation of anti-corrosion coating [27,28] would not meet the conditions necessary for STM. Indeed, XPS spectra of the alumina layer obtained after the 5 h FCA foil annealing on air in muffle operated at 1470 K exhibit the signals from Al and O mainly and C as surface contamination.…”
Section: Selection Of Preparation Conditionsmentioning
confidence: 99%